Loss of UHT milk quality: changes in compositional and physicochemical parameters triggered by different storage conditions (Research, Society and Development, 2022)
The objective of this study was to evaluate some compositional and physicochemical changes that occur during UHT (Ultra-high temperature) milk storage for up to four months. A total of 120 samples of UHT milk were collected from two dairy plants in the state of Minas Gerais, Brazil, and stored under two temperatures (20°C and 30°C) during five periods (0, 30, 60, 90 and 120 days). The experimental design was completely randomized, in a 2x2x5 factorial arrangement, with six replicates per treatment (six batches). Evaluated parameters included fat, total protein, casein, lactose, total solids, solids nonfat (SNF) and milk urea nitrogen (MUN) contents, as well as acidity, density, freezing point and indexes of lipolysis and caseinomacropeptide (CMP). When compared to the Brazilian requirements for UHT milk, the mean values ​​for acidity, fat and SNF contents were in accordance with the standards ​​until the last day of storage. The other parameters are still not covered by the specific UHT milk legislation in Brazil. There was no change of relative density and lactose content also remained constant, except for a decrease at the fourth month. A significant increase, over storage time, in acidity, MUN, lipolysis and CMP indexes occurred. On the other hand, there was a significant decrease in SNF and protein contents. The results showed that there was a gradual loss of quality during UHT milk storage, aggravated by the rise in temperature. These findings demonstrate that UHT milk legislation could be improved by adding parameters such as lipolysis and CMP indexes.